Psychometric validation of the PTSD Checklist-5 among female domestic workers - Hall, Brian J (Archīum Ateneo, 2019)
Migrant populations are at increased risk for exposure to traumatic life events. Presently, there are no reliable and valid screening instruments for posttraumatic stress disorder (PTSD) among Filipino migrant workers, a population that numbers over 2.3 million worldwide. This study evaluated the psychometric properties of the PTSD Checklist for DSM-5 (PCL-5) in a sample of female Filipino migrant workers in Macao (SAR), China, in two studies. The first examined the reliability (internal and test-retest), convergent validity (with depression, anxiety, and rumination), and discriminant validity (with pain and social support) in a sample of 131 participants. The second study established criterion validity of the PCL-5 using the PTSD module of the Mini-International Neuropsychiatric Interview (MINI), delivered by a female Filipino psychologist as the criterion, in a sample of 100 participants. Results indicated excellent internal consistency (Cronbach’s alpha = 0.95) and moderate 10-day test-retest reliability (ρ = 0.58, p < .001). PCL-5 scores correlated strongly with scores on measures of depression (ρ = 0.71, p < .001), anxiety (ρ = 0.61, p < .001), and rumination (ρ = 0.68, p < .001), supporting convergent validity. Discriminant validity was demonstrated by a weaker association with scores on measures of pain (ρ = 0.33, p < .001) and social support (ρ = −0.11, p = .22). The diagnostic accuracy of the scale was good (AUC = 0.87). The optimal cutoff score of 25 optimized sensitivity (0.89) while maintaining adequate specificity (0.73), with a weighted Kappa of κ[1]) = 0.82. Our results demonstrated that the PCL-5 is a reliable and valid screening instrument for use among female Filipino migrant workers.